Screening, characterization and molecular insights of rhamnolipid biosurfactant produced by Pseudomonas aeruginosa BS1 - Nayak, Nisha S.; Joshi, Dhruvi S.; Rathi, Yesha S. (International Journal of Environment, Agriculture and Biotechnology, 2023)
Biosurfactants are a group of heterogenous metabolites synthesized by a variety of microorganisms. They exhibit the properties of the surface tension reduction, emulsion stabilization, promote foaming, and specific activity at extreme temperatures, pH, and salinity. A bacterial strain was screened for its biosurfactant production in 250 ml MSM broth with crude oil as an inducer for 5 days. The screening activity performed by (i) drop collapse test, (ii) oil displacement test, (iii) emulsification index proved the presence of biosurfactant. TLC and FTIR analysis confirmed that the biosurfactant produced by the selected bacterial isolate is a rhamnolipid. The potential isolate was identified by 16S rRNA gene sequencing analysis and it was identified as Pseudomonas aeruginosa.